FENOMENA RUMAH SEDERHANA DI KOTA MEDAN - Silitonga, Shanty; Naibaho, Polin DR (Unika Santo Thomas, 2019)
Affordable houses bloom in Medan due to high demand. Although labeled affordable, there is some contradiction. The primary task of this paper is to compile the various conditions and issues that related to affordable houses in suburban of Medan and to develop its conceptual framework of housing mismatch through literature review gathered. This research uses descriptive qualitative research method. The study found that price factor is the most influencing factor (pull factor) for people to buy the house, followed by affordable installment and attractive building facades.It concluded that there are mismatches between the type of housing unit offered and the group desired by low and middle-income people, location and unhealthy physical conditions.